Kinect hacks: tips y tools for motion and pattern detection tips y herramientas para mover y detectar patrones - Jean, Jared St
Create your own innovative applications in computer vision, game design, music, robotics, and other areas by taking full advantage of Kinect?s extensive interactive, multi-media platform. With this book, you get a step-by-step walkthrough of the best techniques and tools to come out of the OpenKinect project, the largest and most active Kinect hacking community. Learn dozens of hacks for building interfaces that respond to body movements, gestures, and voice, using open source toolkits such as openFrameworks, the Processing IDE, and OpenKinect driver library. Whether you?re an artist, designer, researcher, or hobbyist, this book will give you a running start with Kinect.